The new history in an old museum creating the past at Colonial Williamsburg - Handler, Richard 1950- (Duke University Press, 1997)
The new history in an old museum -- Imag[in]ing colonial Williamsburg -- Why history changes, or, Two theories of history making -- Just the facts -- Social history on the ground -- The company line : aspects of corporate culture at Colonial Williamsburg -- The front line : smile free or die -- Picket lines -- The bottom line
Includes bibliographical references (pages [237]-257) and index. - Description based on print version record
Keywords: Colonial Williamsburg Foundation / History; Colonial Williamsburg Foundation / Management; Colonial Williamsburg Foundation; Geschichte; Williamsburg, Va.